Thou: The connection between Shakespeare and his Sonnets - Gregory Scott Wobser II (The Journal of Undergraduate Research, 2016)
William Shakespeare Sonnet’s were written from an autobiographical point of view that represents his personal struggles with love and. Most notably defining this idea is the use of the word “thou”, that which indicates identity, ownership and things one is owned. Shakespeare uses the friendship with the young man to showcase his desires for love and an everlasting saga for the young man. The spirit of the relationship between the two was perfectly normal for the time period, and a very strong relationship as Shakespeare’s strong language suggests. A relationship that reaches its climax in Sonnet 18, “Shall I compare thee to a summer’s day…..” So was the end of Shakespeare’s struggle with love truly defined in the end of The Sonnets? The world will never know, but poetic art and love can both be present in an autobiographical work, one which truly encompasses the word “thou”.